Black American Perspectives (United States): The Future of Civil Rights, November 11-25, 1991 ([Verlag nicht ermittelbar], 2004)
This study sought to gather Black Americans' perspectives on the effectiveness of Civil Rights Organizations (CROs) and to better understand their views on the future of civil rights in the United States. Respondents were asked a series of questions regarding (1) their attachments to CROs, (2) the effectiveness of CROs and related institutions, (3) future programs of CROs, (4) political and racially based attitudes and beliefs, and (5) social, economic, and demographic measures. The CROs inquired about were the National Association for the Advancement of Colored People (NAACP), the Congress of Racial Equality (CORE), The Urban League, and the Southern Christian Leadership Conference (SCLC). Background information on respondents includes age, highest level of education, and income.